The Effect of non-economic tax payer factors on noncompliance with rental income taxation - Wameyo, Hillary Nalianya (Strathmore University, 2019)
Tax compliance levels in Kenya have remained low, even after use of sanctions such as penalties; armed monitoring, routine audits, fines and closure of non-compliant taxpayers' businesses. Since the introduction of the rental income tax, the taxes from the sector have not grown proportionately to the growth of the economy despite statistics showing the sector to have recorded high growth. This compelled the government to come up with an incentive for any member of the public who voluntarily gives information leading to collection of additional taxes. This still achieved minimal results. The aim of this study was to determine the effect of prevailing tax payer perception of the tax system on noncompliance with rental income taxation in Kenya, to establish the effect of tax payer understanding of the real estate tax regulation on non-compliance with rental income taxation in Kenya and to assess the effect of social norms on non- compliance with rental income taxation in Kenya. The study adopted cross-sectional descriptive survey in which the target population was the taxpayers who had invested in the real estate sector in Nairobi and earn rental income. Convenience sampling was used to select 68 respondents. Data was collected using questionnaires. The study used both descriptive and inferential statistics to analyse the data. Descriptive statistics was used to show the distribution of the responses. The study used the correlation and regression to show the association and the relationship between the variables. Data was presented in tables and figures. The study established that the perception of the respondents was shaped by the government’s inability to provide its citizens with the necessary services such as repair of roads, frequent power outages, water rationing, and poor healthcare services among others. The study further established that the taxpayers’ attitude towards paying tax was bad. This had a direct effect on their rental income tax compliance. The study established that most respondents lacked the knowledge of the rental income tax regulation which was blamed on the lack of proper sensitization by the tax authorities. The study found a direct influence of knowledge of rental income tax regulation on the rental income tax compliance. The study also established that culture influenced the behavior of tax paying. However, peer influence had no influence on the behavior of paying tax. The study recommended that government should ensure it delivers services to its citizens so as to change the perception of the taxpayers towards paying of tax. The government and tax authority in particular should intensify its rental income tax sensitization programme with the aim of making people understand the concept of rental income tax and to enhance tax payment compliance. The government needs to educate its people to love their country and emphasize that payment of tax is everyone’s obligation and beneficial for the development of the country.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Non-compliance; Non-economic factors; Rental income; Tax